Effect of ethylene levels and relative humidity on the storability of 'Gala' apple in controlled atmosphere - Brackmann, Auri; Ceretta, Marcelo (Pesquisa Agropecuaria Brasileira, 1999)
'Gala' apples were stored in controlled atmosphere with 1 kPa O2/3 kPa CO2 at 1°C, with the aim to evaluate the effect of relative humidity (RH) and ethylene removal on fruit quality. Treatments were combinations of ethylene concentration and levels of RH. The relative humidity was maintained around 97% for treatments with high relative humidity and around 94% for treatments with low RH during the two initial and two last months of storage. The treatments with low ethylene concentration were maintained with 0.0 to 1.0 µL/L and 0.0 to 1.5 µL/L whereas the treatment without ethylene removal had about 100 µL/L. After eight months of storage, lowering relative humidity to 94%, during two initial and last storage months showed higher flesh firmness, however with more shriveling at chamber opening and after seven days shelf-life. Internal breakdown and yellowing of fruits were observed with low RH after shelf-life. Ethylene removal maintained higher flesh firmness and retained green ground color and juiciness of fruits after eight months of storage.